1986
DOI: 10.1093/schbul/12.2.274
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Program for Chronic Schizophrenic Patients

Abstract: A 10-week, inhospital holistic health program for male schizophrenic patients was compared with an equally intense social skills training program. The holistic program included training in the stress reduction techniques of exercise and meditation as well as education in stress management. Patients were also encouraged to explore the growth potential of their psychotic experiences and to develop positive beliefs about the outcome of their illness. Both groups showed similar significant decreases in psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 18 publications
0
49
0
1
Order By: Relevance
“…A significant reduction in depression has been found after an aerobic exercise intervention in a combined group of patients suffering from schizophrenia and bipolar disorder, which could possibly interfere with the result (14). Another study found a significant reduction in overall psychopathology using the Psychiatric Assessment Scale (PAS), Nurses Global Impressions Scale (NGI) and Symptom Checklist-90 (SCL-90) (16). The intervention included a combination of different types of sport activities, meditation and stress education.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in depression has been found after an aerobic exercise intervention in a combined group of patients suffering from schizophrenia and bipolar disorder, which could possibly interfere with the result (14). Another study found a significant reduction in overall psychopathology using the Psychiatric Assessment Scale (PAS), Nurses Global Impressions Scale (NGI) and Symptom Checklist-90 (SCL-90) (16). The intervention included a combination of different types of sport activities, meditation and stress education.…”
Section: Discussionmentioning
confidence: 99%
“…included in the meta-analysis (e.g., Lukoff, Wallace, Liberman, & Burke, 1986;Wallace & Liberman, 1985).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The latter two categories are not covered here as they are beyond the scope of this article. [Lukoff et al 1986;Pelham et al 1993;Fogarty and Happell, 2005;Eldridge et al 2011]. An RCT comparing wellbeing training with standard care showed improved rates of selfreported heath status following a 12-month wellness training intervention [Chafetz et al 2008].…”
Section: Study Selectionmentioning
confidence: 99%